Melonz: watermelon rinds’ cereals / Che Wan Nur Shahirah Che Wan Mohd Noor ... [et al.] - Che Wan Mohd Noor, Che Wan Nur Shahirah; Zubir, Fatin Nur Syamimi; Ramli, Nur Aishah Solehah; Izhar, Saidatul Husna; Yosree, Deena Akmaliah (2023)
The BigBites Enterprises company was aiming to produce a new product called Melonz, a healthy-based cereal. Melonz contains the watermelon rind as the primary ingredient which is known as a source of vitamins, iron, calcium, and fibers. Melonz, which is red in color with a triangle shape that is coated with honey will attract varieties level of ages, like kids, travellers, adults, students, and workers. The cereals is made up to help people to make their life easier with our ready-to-eat product. The cereal’s packaging uses a zip lock gusset bag as primary packaging in order to ensure the shelf life of the product can be extended up to a year. The cereal itself was shaped in a triangle shape that symbolizes the triangle shape of the watermelon. Our target markets are kids, teenagers, students, as well as workers. We wish to make everyone able to have their breakfast despite having a busy daily routine. The consumers can bring along our cereals product and eat it while they are on their way to school, class, or work. Our product is convenient to eat as it is already coated with honey to give a sweet taste without having to eat it with fresh milk. There are plenty of companies that already have produced cereals products in the market. However, our company challenges ourselves to compete with the existing companies in this market as we are confident that our product is different from other existing products such as MILO, KoKo Krunch, Froot Loops, and many more. Through thorough research, surveys, and accumulated complaints, we developed Melonz based on the publics’ opinions and requests. Since the existing cereals products in the market often need to be consumed with fresh milk, we believe that we can be on a higher level than the existing products.